Elucidation of the Potential Hair Growth-Promoting Effect of Botryococcus terribilis, Its Novel Compound Methylated-Meijicoccene, and C32 Botryococcene on Cultured Hair Follicle Dermal Papilla Cells Using DNA Microarray Gene Expression Analysis - Aprill Kee Oliva; Meriem Bejaoui; Atsushi Hirano; Takashi Arimura; Tran Ngoc Linh; Eriko Uchiage; Sachiko Nukaga; Kenichi Tominaga; Hiroyuki Nozaki; Hiroko Isoda (Biomedicines, 2022)
A person’s quality of life can be adversely affected by hair loss. Microalgae are widely recognized for their abundance and rich functional components. Here, we evaluated the hair growth effect of a green alga, Botryococcus terribilis (B. terribilis), in vitro using hair follicle dermal papilla cells (HFDPCs). We isolated two types of cells from B. terribilis—green and orange cells, obtained from two different culture conditions. Microarray and real time-PCR results revealed that both cell types stimulated the expression of several pathways and genes associated with different aspect of the hair follicle cycle. Additionally, we demonstrated B. terribilis’ effect on collagen and keratin synthesis and inflammation reduction. We successfully isolated a novel compound, methylated-meijicoccene (me-meijicoccene), and C32 botryococcene from B. terribilis to validate their promising effects. Our study revealed that treatment with the two compounds had no cytotoxic effect on HFDPCs and significantly enhanced the gene expression levels of hair growth markers at low concentrations. Our study provides the first evidence of the underlying hair growth promoting effect of B. terribilis and its novel compound, me-meijicoccene, and C32 botryococcene.